Privacy‐preserving cloud‐fog–based traceable road condition monitoring in VANET. Issue 2 (11th February 2020) - Wang, Wei; Wu, Lei; Qu, Wenlei; Liu, Zhaoman; Wang, Hao
Summary: With the development of intelligent vehicles, the research on road condition monitoring has attracted much attention in the vehicular ad hoc network (VANET). The combination of VANET, cloud computing, and fog computing provides on‐demand computational resources while creating a lot of new challenges. In this paper, we propose an efficient privacy‐preserving cloud‐fog–based traceable road surface condition monitoring scheme. We use certificateless aggregate signcryption technology to implement multiple messages aggregation verification, which greatly saves computing resources and bandwidth. Moreover, we also use a traceable vehicle pseudo identity generated by a trace authority (TRA) to achieve identity privacy protection. To ensure the privacy of the fog and cloud server, the road condition information is reported in ciphertext format. In addition, the cloud server can perform ciphertext equivalence test operation to distinguish different road condition information of the same area without compromising the confidentiality. The ciphertext, which exceeds the set threshold, is uploaded to the blockchain. It can be stored permanently and never be tampered with or deleted. Finally, we demonstrate the correctness of the proposed scheme and show that the proposed scheme has higher efficiency. Abstract : In this paper, we propose an efficient privacy‐preserving cloud‐fog–based traceable road surface condition monitoring scheme using certificateless aggregate signcryption technology to implement multiple messages aggregation verification. Moreover, we use a traceable vehicle pseudo identity generated by a trace authority (TRA) to achieve identity privacy protection. We show that the proposed scheme is more efficient with meeting more functional requirements.